Anterior access to the cervicothoracic junction via partial sternotomy: a clinical series reporting on technical feasibility, postoperative morbidity, and early surgical outcome - Issa, Mohammed; Neumann, Jan-Oliver; Maisary, Sameer al-; Dyckhoff, Gerhard; Kronlage, Moritz; Kiening, Karl; Ishak, Basem; Unterberg, Andreas; Scherer, Moritz (Journal of Clinical Medicine, 2023)
Surgical access to the cervicothoracic junction (CTJ) is challenging. The aim of this study was to assess technical feasibility, early morbidity, and outcome in patients undergoing anterior access to the CTJ via partial sternotomy. Consecutive cases with CTJ pathology treated via anterior access and partial sternotomy at a single academic center from 2017 to 2022 were retrospectively reviewed. Clinical data, perioperative imaging, and outcome were assessed with regards to the aims of the study. A total of eight cases were analyzed: four (50%) bone metastases, one (12.5%) traumatic instable fracture (B3-AO-Fracture), one (12.5%) thoracic disc herniation with spinal cord compression, and two (25%) infectious pathologic fractures from tuberculosis and spondylodiscitis. The median age was 49.9 years (range: 22-74 y), with a 75% male preponderance. The median Spinal Instability Neoplastic Score (SINS) was 14.5 (IQR: 5; range: 9-16), indicating a high degree of instability in treated cases. Four cases (50%) underwent additional posterior instrumentation. All surgical procedures were performed uneventfully, with no intraoperative complications. The median length of hospital stay was 11.5 days (IQR: 9; range: 6-20), including a median of 1 day in an intensive care unit (ICU). Two cases developed postoperative dysphagia related to stretching and temporary dysfunction of the recurrent laryngeal nerve. Both cases completely recovered at 3 months follow-up. No in-hospital mortality was observed. The radiological outcome was unremarkable in all cases, with no case of implant failure. One case died due to the underlying disease during follow-up. The median follow-up was 2.6 months (IQR: 23.8; range: 1-45.7 months). Our series indicates that the anterior approach to the cervicothoracic junction and upper thoracic spine via partial sternotomy can be considered an effective option for treatment of anterior spinal pathologies, exhibiting a reasonable safety profile. Careful case selection is essential to adequately balance clinical benefits and surgical invasiveness for these procedures.
Gesehen am 16.08.2023